2004
DOI: 10.1080/17402520400001686
|View full text |Cite
|
Sign up to set email alerts
|

Early Appearance of TNF‐α and Other Cytokines in Bronchus Associated Lymphoid Tissues (BALT) from Growing Wistar Rats. What is the Role of TNF‐α?

Abstract: Several different cytokines trigger the development of determined cell subsets in BALT of growing Wistar rats. Early appearance (4 days post partum) of gdT cells in BALT has been shown, as well as its role in up-regulating TNF-a production. In the present report, we studied in the BALT: (1) the profile of the cytokines, TNF-a, INF-g and IL-10 and (2) in TCR gdþ cells, the existence of a colocalization with TNF-a as well as with INF-g. All the cytokines studied were observed at an early stage of BALT developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…IL‐6 is a glycoprotein with a molecular mass in the 21‐ to 28‐kD range, depending on the cell source and mode of preparation (Akira et al., ; Heinrich et al., ; Suzuki et al., ; Chagnon et al., ). The anti‐TNF‐α antibody specifically labels 51 kDa TNF trimer (Delettieres et al., ). After three washes in 0.1% TBS‐Tween 20, the membranes were then incubated with a horseradish peroxidase‐conjugated goat anti‐mouse secondary antibody (1:20000; Jackson ImmunoResearch, Baltimore, MD, USA) or goat anti‐rabbit secondary antibody (1:20000; Jackson ImmunoResearch) for 1 h at room temperature, and washed three times.…”
Section: Methodsmentioning
confidence: 99%
“…IL‐6 is a glycoprotein with a molecular mass in the 21‐ to 28‐kD range, depending on the cell source and mode of preparation (Akira et al., ; Heinrich et al., ; Suzuki et al., ; Chagnon et al., ). The anti‐TNF‐α antibody specifically labels 51 kDa TNF trimer (Delettieres et al., ). After three washes in 0.1% TBS‐Tween 20, the membranes were then incubated with a horseradish peroxidase‐conjugated goat anti‐mouse secondary antibody (1:20000; Jackson ImmunoResearch, Baltimore, MD, USA) or goat anti‐rabbit secondary antibody (1:20000; Jackson ImmunoResearch) for 1 h at room temperature, and washed three times.…”
Section: Methodsmentioning
confidence: 99%
“…The role of cytokines in the development of BALT has been studied in rats, where already by day 4 after birth, tumor necrosis factor (TNF) was present in BALT (38). At day 4 in rats, Marquez et al (39) concluded that all necessary T‐cell phenotypes were present.…”
Section: Ontogenymentioning
confidence: 99%
“…However, we did not find evidence of direct injury to lung tissue. TNF-a has also been implicated in the development of BALT, and is known to play a role in lymph node homeostasis (29,30). The increase in CD4…”
mentioning
confidence: 99%